PENYULUHAN HUKUM: PENCEGAHAN PERNIKAHAN USIA DINI MENYIAPKAN GENERASI EMAS DI DESA PENUJAK, KABUPATEN LOMBOK TENGAH, PROVINSI NUSA TENGGARA BARAT - Anugerahayu, Ayang Afira; S, Nathania Permata (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Early marriage is a multidimensional problem that hinders the fulfillment of children's and women's rights in Indonesia, especially in West Nusa Tenggara (NTB) province, which has a high prevalence rate (14.23% in 2023) compared to the national average (8.06%). This practice is rooted in economic factors, local traditions, and low legal awareness, which leads to serious consequences for health, education, and socioeconomic aspects. Therefore, legal counseling in Penujak Village, Central Lombok, which still holds strong traditional values, is a strategic step to increase public awareness about the risks of early marriage and the importance of child protection. This activity was conducted on September 4, 2025, at the Penujak Village Hall using a participatory method. The goal was to provide legal understanding and education through presentations and interactive discussions involving village officials, religious leaders, traditional leaders, parents, and teenagers. The results of this activity showed an increase in understanding and collective awareness among participants, evidenced by their enthusiasm in discussions and their commitment to supporting early marriage prevention efforts. Participants realized that delaying the age of marriage is a long-term investment to achieve a healthy, intelligent, and competitive